Icariin Improves Age-Related Testicular Dysfunction by Alleviating Sertoli Cell Injury via Upregulation of the ERα/Nrf2-Signaling Pathway - Zhao, Haixia; You, Xu; Chen, Qian; Yang, Siqi; Ma, Qiongyan; He, Yumin; Liu, Chaoqi; Dun, Yaoyan; Wu, Jie; Zhang, Changcheng; Yuan, Ding (Frontiers in Pharmacology, 2020)
Sertoli cells play crucial roles in spermatogenesis and are impaired by aging. Icariin, a flavonoid from Epimedium, has been reported to exhibit anti-aging effects and improve testicular dysfunction in the clinical setting. However, whether icariin improves age-related degeneration of testicular function via protection from Sertoli cell injury remains unclear. In the present study, we evaluated the protective effect of icariin on Sertoli cell injury and explored the possible mechanism(s) in vivo and in vitro. Dietary administration of icariin for 4 months significantly ameliorated the age-related decline in testicular function by increasing testicular and epididymal weights and indices, sperm count and sperm viability, testicular testosterone and estradiol concentrations, and seminiferous tubule diameters and heights. In addition, icariin protected age-related Sertoli cells from injury as evidenced by an analysis of Sertoli cell number, ultrastructure, and function. Such changes were accompanied by upregulation of ERα and Nrf2 signaling in Sertoli cells. Parallel in vitro studies also demonstrated that icariin inhibited untoward effects on the TM4 mouse Sertoli cell line with concomitant upregulation of ERα and Nrf2 signaling. Conversely, ERα siRNA reversed icariin-mediated protection of Sertoli cell injury. Our data suggest that icariin effectively ameliorates age-related degeneration of testicular function by alleviating Sertoli cell injury via the ERα/Nrf2 signal-transduction pathway. Thus, mitigating Sertoli cell damage via the ERα/Nrf2 signaling pathway likely represents a promising strategy for the prevention of age-related testicular dysfunction.